Biology of <i>Trypanosoma Cruzi</I> 2019
DOI: 10.5772/intechopen.84733
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture and Maintenance of the Evolutionary Forms of Trypanosoma cruzi for Studies of Parasitic Biology

Abstract: This chapter aims to present and discuss the main cell culture techniques used for the growth and maintenance of the different evolutionary forms of the protozoan Trypanosoma cruzi, the etiologic agent of the Chagas disease. Chagas disease is a neglected tropical disease endemic in several Latin American countries. Here, we intend to present the main difficulties, advantages, and disadvantages of using Trypanosoma cruzi cell culture in parasitic biology. Finally, we present the main research opportunities in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Remarkably, in vitro infections showed that the percentage of "dormant" amastigotes of strains belonging to hybrid DTUs TcV and TcVI was higher when compared to non-hybrid DTU strains TcI and TcII [45]. Depending on the research objectives, various parasite stages are utilized in in vitro assays, including, epimastigotes grown in axenic medium; trypomastigotes obtained from the supernatant of mammalian cultured cells; metacyclic trypomastigotes derived from epimastigote differentiation; and intracellular amastigotes [46]. In these studies, both polyclonal strains and isolated clones have been used.…”
Section: Intrinsic Characteristics Of the Dtusmentioning
confidence: 99%
“…Remarkably, in vitro infections showed that the percentage of "dormant" amastigotes of strains belonging to hybrid DTUs TcV and TcVI was higher when compared to non-hybrid DTU strains TcI and TcII [45]. Depending on the research objectives, various parasite stages are utilized in in vitro assays, including, epimastigotes grown in axenic medium; trypomastigotes obtained from the supernatant of mammalian cultured cells; metacyclic trypomastigotes derived from epimastigote differentiation; and intracellular amastigotes [46]. In these studies, both polyclonal strains and isolated clones have been used.…”
Section: Intrinsic Characteristics Of the Dtusmentioning
confidence: 99%